2018
DOI: 10.1002/cncr.31856
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nonfounder BRCA1/2 mutations in Ashkenazi Jewish patients presenting for genetic testing at a hereditary breast and ovarian cancer center

Abstract: BACKGROUND: Genetic assessment in Ashkenazi Jewish (AJ) patients often is limited to BRCA1/2 founder mutation testing. With access to time-efficient and cost-efficient multigene panel testing, some advocate expanding genetic testing in this population. However, to the best of the authors' knowledge, rates of nonfounder BRCA1/2 mutations and mutations in cancer-associated genes other than BRCA1/2 among AJ are not known. In the current study, the authors sought to assess the prevalence of mutations other than BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
9
0
2
Order By: Relevance
“…founder mutations [12]. Extensive analyses have revealed that somatic BRCA1 mutations are uncommon in unselected patients, although expression of BRCA1 is often reduced, in non-hereditary (sporadic) BC [10,[12][13][14][15]. BRCA mutation and hormone receptor status are also interlinked.…”
Section: Dna Repair Parp Inhibition and Synthetic Lethalitymentioning
confidence: 99%
See 1 more Smart Citation
“…founder mutations [12]. Extensive analyses have revealed that somatic BRCA1 mutations are uncommon in unselected patients, although expression of BRCA1 is often reduced, in non-hereditary (sporadic) BC [10,[12][13][14][15]. BRCA mutation and hormone receptor status are also interlinked.…”
Section: Dna Repair Parp Inhibition and Synthetic Lethalitymentioning
confidence: 99%
“…Germline BRCA (gBRCA) mutations are particularly common in certain populations. For example, in a study of 732 women of Ashkenazi Jewish heritage who underwent genetic testing, 11% had one of three gBRCA founder mutations [ 12 ]. Extensive analyses have revealed that somatic BRCA1 mutations are uncommon in unselected patients, although expression of BRCA1 is often reduced, in non-hereditary (sporadic) BC [ 10 , 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] The well-known founder mutations are BRCA1 185delAG, 5382insC and BRCA2 6174delT, 5,6 the three founder mutations account for more than 78% of BRCA1/2 pathogenic variants in the Ashkenazi Jewish population. 7,8 Other founder mutations have also been reported in Iceland (BRCA2 c.771_775del), 9 the Netherlands (BRCA1 c.2685_2686del) 10 and Sweden (BRCA1 c.3052_3053insTGAGA). 11 Despite the availability of substantial information regarding BRCA1/2 founder mutations in Caucasians, 4 the information available on BRCA1/2 founder mutations in Chinese Han is extremely limited.…”
Section: Introductionmentioning
confidence: 99%
“…Most BRCA1/2 founder mutation studies have been conducted in Caucasians . The well‐known founder mutations are BRCA1 185delAG, 5382insC and BRCA2 6174delT, the three founder mutations account for more than 78% of BRCA1/2 pathogenic variants in the Ashkenazi Jewish population . Other founder mutations have also been reported in Iceland ( BRCA2 c.771_775del), the Netherlands ( BRCA1 c.2685_2686del) and Sweden ( BRCA1 c.3052_3053insTGAGA) …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been documented since several decades that Jewish women suffer from a genetic predisposition for BC. Ashkenazi Jewish patients, in fact, often develop a genetic (mutations in BRCA 1 and BRCA 2) or familial form of BC or ovarian cancer (42). Moreover, their response to chemoradiation can be less effective than the one registered in the rest of population (43).…”
Section: Resultsmentioning
confidence: 99%